Evaluation of the cytotoxicity of new formulations of cariostatic agents containing nano silver fluoride: an in vitro study - Espíndola-Castro, Luís Felipe; de Oliveira Ribeiro, Rafael Antonio [UNESP]; de Souza Costa, Carlos Alberto [UNESP]; Rosenblatt, Aronita; Galembeck, André; de Melo Monteiro, Gabriela Queiroz (Springer Nature, 2025)
The objective of the study was to assess the indirect cytotoxicity of 600 ppm and 1500 ppm nano silver fluoride (NSF) compared to other commercial cariostatic agents. 56 dentin discs with 0.4 mm in thickness were obtained from intact human molars and adapted to artificial pulp chambers (APCs). The discs were divided into seven groups according to treatment (n = 8): no treatment (positive control—PC), 29% hydrogen peroxide (negative control—NC), 30% Cariestop (CS30), 38% Riva Star (RS38), 38% Advantage Arrest (AA38), 600 ppm NSF (NSF600), and 1500 ppm NSF (NSF1500). The cariostatic agents were applied on the occlusal surface of the dentin discs (facing upward), and the pulp surface (facing downward) remained in contact with the culture medium. Immediately after the treatments, the extracts (DMEM + cariostatic agent components diffused through the discs) were collected and applied to MDPC-23 cells, which were assessed for viability (CV—alamarBlue, live/dead), adhesion/spreading (F-actin), alkaline phosphatase (ALP) activity, and mineralization nodule (MN) formation. The data were statistically analyzed by ANOVA/Games–Howell (p = 0.05). CV and ALP activity in CS30, RS38, AA38, and NSF600 were similar to PC (p > 0.05). MN formation significantly decreased only in NC, CS30, RS38, and AA38 compared to PC (p < 0.001). Only NSF600 and NSF1500 did not differ from PC (p > 0.05) with mineralization nodules, and this specific cell activity significantly decreased in all other groups (p < 0.05). NSF solutions (600 ppm and 1500 ppm) did not cause transdentinal toxicity on MDPC-23 cells.
Keywords: Cariostatic agents; Cytotoxicity; Dental caries; Dental pulp